Analisis Tipelogi Perubahan Kelembagaan Kesbangpol Kabupaten Serang Analysis of Typology of Institutional Changes in Kesbangpol Serang Regency - hakim, agus lukman (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2022)
Government Regulation (PP) No. 18 of 2016 concerning Regional Apparatus technical constraints related to institutional synchronization of Regional Apparatus. One of them is related to the existence of the National and Political Unity institution which is part of the regional secretariat under the coordination of Regional Assistant I Serang Regency which is regulated in detail by Regional Regulation No. 10 of 2018 concerning Amendments to the Regional Regulation of Serang Regency No. 11 of 2016 concerning the Establishment and Composition of the Serang Regency Regional Apparatus. This study is a qualitative descriptive study with the aim of providing an overview of the typology of the Kesbangpol institutional structure in accordance with applicable regulations.The results showed that based on general and technical factor assessments of mapping the intensity of government affairs and determining the workload of the Kesbangpol Government of Serang Regency, a score of 800 was obtained. Thus, Kesbangpol can be used as an Agency with type A with a large workload scale. Based on regional financial considerations and the limited availability of apparatus owned by the Serang Regency Government, the type of Kesbangpol institution can be reduced to a level below it, with type B. 100 - 441 of 2019 concerning the nomenclature of regional apparatus that carries out government affairs in the field of national unity and politics with 3 types of fields, namely: a) The fields of ideology, national insight and economic, socio-cultural, religious resilience; b) Domestic politics and community organizations; c) The field of national awareness and conflict management.